Expert Consensus On The Development Of An Islamic Creative Media Model Through The Fuzzy Delphi Method - Rosmawati Mohamad Rasit; Muhamad Faisal Ashaari; Khazri Osman; S. Salahudin Suyurno; Eizan Azira Mat Sharif; Mohammad Asraf Muslim; Muhammad Amirul Nor Faizal (Pakistan Journal of Life and Social Sciences, 2024)
Pakistan Journal of Life and Social Sciences Volume 21 Issue 2 Page (869-883)